2006
DOI: 10.2174/187153006777442404
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Function in Severe Sepsis

Abstract: Sepsis and septic shock continue to be a major cause of morbidity and mortality in critically ill patients. During the onset of sepsis, several inflammatory mediators, including cytokines, chemokines and nitric oxide are released systemically and mediate most of the pathophysiological events present in sepsis and septic shock, such as cardiovascular dysfunction and target-organ lesions. Polymorphonuclear leukocytes are critical effector cells during the inflammatory process and their migration to the infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 0 publications
0
37
0
1
Order By: Relevance
“…Previous studies have revealed the presence of hyperglycemia, neutrophilia or lymphopenia in patients with sepsis (Alves-Filho et al 2006;Corstjens et al 2006;Giamarellos-Bourboulis 2010). However, the presence of these three alterations together in a same group of patients has not been reported yet.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have revealed the presence of hyperglycemia, neutrophilia or lymphopenia in patients with sepsis (Alves-Filho et al 2006;Corstjens et al 2006;Giamarellos-Bourboulis 2010). However, the presence of these three alterations together in a same group of patients has not been reported yet.…”
Section: Discussionmentioning
confidence: 90%
“…We know that the function of these cells is essential in the innate immunological response to the tissue injury. Some studies have shown impaired functions of neutrophils during sepsis (Alves-Filho et al 2006Giamarellos-Bourboulis 2010). On the other hand, some changes in neutrophil functions have been described in healthy patients after oral administration of a glucose load (Mohanty et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, PTX could afford protection by its effects on inflammatory cells. Studies evaluating the effects of PTX on adhesion molecule expression have shown decreased P-selectin expression after hemorrhagic shock and decreased proinflammatory cytokine-induced ICAM-1 expression in human pulmonary epithelial cells and polymorphonuclear leukocytes (11,17,37).…”
Section: Discussionmentioning
confidence: 99%
“…Animals develop progressive bacteremia, with the release of multiple cytokines and chemokines into plasma, hypermetabolism, fever/ hypothermia, and other clinical features similar to those found in humans with sepsis (11). The main property of the lungs, gas exchange, combined with their delicate anatomical architecture, render them vulnerable during sepsis.…”
Section: Is Oliveira-junior Et Almentioning
confidence: 99%
See 1 more Smart Citation